Retrospective study of canine mast cell tumor using two histopathological classification - De Carvalho, Anna Paula Martins; Nogueira, Gabriella Massine; Leandro, Hassan Jerdy; Medina, Raphael Mansur; De Carvalho, Eulógio Carlos Queiróz; De Nardi, Andrigo Barbosa [UNESP]; Da Silveira, Leonardo Serafim (Revista Brasileira de Medicina Veterinaria, 2017)
The number of reported cancer in dogs is increasing every year and the mast cell tumor is the most common skin tumor. There are few reports regarding tumor characteristics in Brazil. This study aimed to conduct a retrospective study of animals with mast cell tumors treated at the Veterinary Hospital of UENF. Evaluation of gender, breed, age, tumor location and histological grade by Kiupel and Patnaik was ratings of 61 animals. Males were majority (59%) of animals and elderly patients aged between 7 and 12 years were the most affected. Most dogs were mixed breed, Boxer, Labrador and Pinscher. The region members (38.5%), followed by tumors in the trunk (27%) and genital tumors (13.1%) were the most common tumor localization. Animals with multiple tumors were also reported (13.4%). Six tumors were classified as grade I, 45 grade II and 10 as grade III. According to Kiupel classification, most tumors (68.85%) were classified as low grade. By this study it can be seen that the older animals were the most affected, race and location are related to the histological grade and the most common were the grade II and the low grade.
Estudo retrospectivo do mastocitoma cutâneo canino utilizando duas classificações histopatológicas
Keywords: Dog; Histopathology; Kiupel; Mast cell tumor; Patnaik